2010
DOI: 10.1038/cdd.2010.55
|View full text |Cite
|
Sign up to set email alerts
|

Omi/HtrA2 is a positive regulator of autophagy that facilitates the degradation of mutant proteins involved in neurodegenerative diseases

Abstract: Omi, also known as high temperature requirement factor A2 (HtrA2), is a serine protease that was originally identified as a proapoptotic protein. Like Smac/Diablo, it antagonizes inhibitor of apoptosis proteins when released into the cytosol on apoptotic stimulation. Loss of its protease activity in mnd2 (motor neuron degeneration 2) mice is associated with neurodegeneration. However, the detailed mechanisms by which Omi regulates the pathogenesis of neurodegenerative disease remain largely unknown. We report … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(76 citation statements)
references
References 40 publications
3
72
1
Order By: Relevance
“…12 Moisoi et al 30 showed that HtrA2 is necessary for preventing accumulation of unfolded protein and oxidative stress in mitochondria. A recent study by Li et al 31 reported that HtrA2 is responsible for the maintenance of constitutive autophagy, which can eliminate damaged mitochondria. The exact protective mechanisms of HtrA2, especially under ischemic stress, remain unclear and warrant further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…12 Moisoi et al 30 showed that HtrA2 is necessary for preventing accumulation of unfolded protein and oxidative stress in mitochondria. A recent study by Li et al 31 reported that HtrA2 is responsible for the maintenance of constitutive autophagy, which can eliminate damaged mitochondria. The exact protective mechanisms of HtrA2, especially under ischemic stress, remain unclear and warrant further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, although Hax-1 protein levels were decreased in cells exposed to OGD/R ( Figure 1C), transcription of Hax-1 was not altered (Figure 1D), suggesting a post-translational process of Hax-1. As we previously found that Omi cleaves Hax-1 [24] and that Hax-1 is degraded by the ubiquitin-proteasome pathway after apoptotic stimulation [26] , we performed experiments using a cellular OGD/R model to address how Omi regulates Hax-1 after I/R. In N2a cells that were exposed to OGD/R, an increase of Omi and a decrease of Hax-1 were observed, however, Hax-1 protein levels were dramatically increased after Omi was knocked down (Figure 1E), suggesting that Omi possibly processes Hax-1.…”
Section: Resultsmentioning
confidence: 76%
“…The Hax-1 related constructs were generated as previously described [24] . Briefly, full length Hax-1 cDNA was amplified from a human fetal brain library (Invitrogen) with the primers 5'-GCGAATTCACCATGAGCCTCTTTGATCTCTTC-3' and 5'-ATGTCGACATCCGGGACCGGAACCAACGTCCC-3', and inserted into a pEGFP-N1 (Clontech, Mountain View, CA, USA) vector at the Hind III and Sal I sites.…”
Section: Plasmidsmentioning
confidence: 99%
“…The oligonucleotides targeting Omi sequences (si-Omi) and the negative control (NC) siRNA have been described previously [27] . The oligonucleotides to target sequences of E2F1 were purchased from Ribobio (Guangzhou, China) and their sequences were as follows: si-E2F1 sense 5'-GGAUCUGGAGACUGACCAU-3', antisense 5'-AUGGUCAGUCUCCAGAUCC-3'.…”
Section: Rna Interferencementioning
confidence: 99%
“…The Omi-related plasmids have been described previously [27] . Full-length human E2F1 complementary DNA (cDNA) was amplified using PCR from a human fetal brain cDNA library with the primers 5'-GAGGATCCCCATG-GCCTTGGCCGGGGCC-3' and 5'-GAGAATCCCGAAATC-CAGGGGGTGA-3'.…”
Section: Plasmidsmentioning
confidence: 99%